As escritoras de grafite de Porto Alegre: um estudo sobre as possibilidades de formação de identidade através dessa arte - Silva, Vivian (2008)
This dissertation aims to analyze the formation of social identity of grafiteiras of Porto Alegre. These writers of streets print in walls one practical of identity construction, as women conquering space in a predominantly masculine territory until then - the world of the graphite and hip hop. You can see the graffiti as an expression of socio-cultural increasingly widespread in the wall of the metropolis. When walking through the streets of the city realizes is that the girls involved have similarities in their pieces of clothing and slang; identify themselves with audiovisual elements in their everyday experiences. The data from this research are themselves in oral sources, through semi-structured interviews, that after his transcript is reviewed by analysing the content. The technique of interview is used to hold talks with the audience on a range of topics enabling reach the constructive elements of the identities of these young people. They are used authors of Social Sciences as Erving Goffman, Manuel Castells, Stuart Hall that reflect on the notion of identity.